MICROBIAL CONTAMINATION AND ANTIBIOTIC RESISTANCE IN SELECTED YOGHURT BRANDS IN ELELE, RIVERS STATE, NIGERIA - ANAGBOSO, Martin; Ohaebuka, Chioma; Mbah, Edith; Osuala, Oluchi; DAOKORU-OLUKOLE, Chidinma; AGEDAH, Ebisomu; Onu, Euslar; Nwankwo, Grace; Okafor, Freda; Okonko, Iheanyi (Covenant Journal of Physical and Life Sciences, 2024)
Yogurt, a widely consumed fermented dairy product, offers numerous nutritional benefits but is susceptible to microbial contamination, posing potential public health risks. This study evaluates the microbial contamination in twelve brands of yogurt sold in Elele, Rivers State, Nigeria, analyzing ambient and frozen samples. The results revealed higher bacterial loads in yogurt stored at room temperature, with Bacillus sp (40%) being the most prevalent contaminant, followed by Lactobacillus bulgaricus (30%) and Salmonella sp (35%)., the latter of which is particularly concerning due to its potential to cause foodborne illnesses. Additionally, antibiotic susceptibility testing demonstrated that the isolated bacteria exhibited significant multi-drug resistance, especially Salmonella sp., which was resistant to eight of ten antibiotics tested. These findings highlight the importance of proper storage conditions, strict hygiene practices, and the need for enhanced safety measures during yogurt production to minimize health risks associated with contaminated yogurt products.